Subglottic stenosis in Wegener's granulomatosis: development during cyclophosphamide treatment with response to carbon dioxide laser therapy. Issue 4 (April 1990) - Strange, C; Halstead, L; Baumann, M; Sahn, S A
Abstract : A patient with Wegener's granulomatosis rapidly developed a circumferential subglottic stenosis while on a cyclophosphamide regimen that had caused resolution of systemic symptoms and pulmonary infiltrates. The stenosis developed in the area of previously noted tracheal ulceration and responded satisfactorily to carbon dioxide laser therapy.